Taxonomic status of some species of Aspidostomatidae (Bryozoa, Cheilostomata) from the Oligocene and Miocene of Patagonia (Argentina) - Pérez, Leandro Martín (2018)
The bryozoan genus Aspidostoma Hincks, 1881 has been regarded as the only representative of the Aspidostomatidae Jullien, 1888 in Argentina to date. Its type species, Aspidostoma giganteum (Busk, 1854), is presently distributed in the Magellanic Region (Argentina and Chile) and has been recorded in Oligocene and Miocene fossil deposits of Santa Cruz and Chubut, respectively. New material from San Julián (late Oligocene), Monte León (early Miocene), Chenque (early to middle Miocene), and Puerto Madryn (late Miocene) formations suggests, however, that A. giganteum is not represented in the fossil record. Material from Puerto Madryn Formation previously regarded as A. giganteum is here recognized as Aspidostoma roveretoi new species. Aspidostoma ortmanni Canu, 1904 is revalidated for the species from the San Julián Formation. Aspidostoma armatum new species and Aspidostoma tehuelche new species are introduced for material from the Monte León and Chenque formations, respectively. Aspidostoma incrustans Canu, 1908, from the early Miocene, is redescribed. Melychocella Gordon and Taylor, 1999, which differs from Aspidostoma in having vicarious avicularia and lacking a median ridge and a quadrangular process proximal to the opesia-orifice, is so far represented by three Paleogene species from the Chatham Islands (Southwest Pacific). The material from Monte León allowed us to transfer Aspidostoma flammulum Canu, 1908 to Melychocella, resulting in the new combination Melychocella flammula (Canu, 1908). Melychocella biperforata new species is described from the lower Miocene Monte León and Chenque formations. The presence of Melychocella in the Neogene of Patagonia extends its geographic distribution and its temporal range.